Nonunion of Transpsoas Lateral Lumbar Interbody Fusion Using an Allograft: Clinical Assessment and Risk Factors - Satake, Kotaro (Spine Surg Relat Res, 2018)
INTRODUCTION: This retrospective study was performed to evaluate the clinical influence of - and to identify the risk factors for nonunion of transpsoas lateral lumbar interbody fusion (LLIF) with use of allograft. METHODS: Sixty-three patients who underwent transpsoas LLIF (69.8 ± 8.9 years, 21 males and 42 females, 125 segments) were followed for a minimum 2 years postoperatively. For all LLIF segments, polyetheretherketone (PEEK) cages packed with allogenic bone were applied with supplemental bilateral pedicle screws (PSs). Bone bridge formation was evaluated by computed tomography (CT) 2 years postoperative, and a segment without any bridge formation was determined to be a nonunion. Sixty-one participants (96.8%) were classified into two groups for clinical evacuation: Group N that contained one or more nonunion segments and Group F that contained no nonunion segment. Visual analogue scales (VAS) scores and the effective rates of the five domains of the Japanese Orthopedic Association Back Pain Evaluation Questionnaire (JOABPEQ) were compared between Groups N and F. The risk factors for nonunion were determined by univariate and multivariate analyses. RESULTS: Twenty segments (16%) were diagnosed as nonunion. There were no significant differences in all VAS scores, and the ratio of effective cases in all domains of JOABPEQ between Group N (n = 14) and F (n = 47). Multivariate analysis identified percutaneous PS (PPS) usage (odds ratio [OR]: 3.14, 95% confidence interval: 1.13-8.68, p = 0.028) as a positive risk factor for nonunion. CONCLUSIONS: We should be aware of the higher nonunion rate in the LLIF segments supplemented with PPS, though nonunion does not affect significantly clinical outcomes at 2 years postoperative.